Physical exercise and cognition in older adults, a scientific approach scanty reported in Latin America and Caribbean populations - Jiménez-Maldonado, Alberto; Rentería, Iván; Johnson, David K.; Moncada-Jiménez, José; García-Suárez, Patricia C. (Frontiers in Sports and Active Living, 2024)
The advancement of public services, including the increased accessibility of health services, has led to a rise in life expectancy globally. As a result, aging populations are becoming more prevalent, raising concerns about cognitive decline. Fortunately, non-pharmacological methods, such as physical exercise, have been shown to mitigate the effects of aging on the brain. In this perspective article, we examined meta-analyses on the impact of physical exercise on cognition in older adults. The results indicate that combined exercise (i.e., aerobic plus strength training), has a significant positive effect on overall cognition and executive function. However, we found a lack of scientific studies on this topic in Latin American and Caribbean countries. Therefore, there is a pressing need for research to identify the feasibility of physical exercise interventions to improve cognitive skills in older adults from these regions.